Meta-análise de parâmetros genéticos relacionados ao consumo alimentar residual e a suas características componentes em bovinos - Del Claro, Ana Cecilia; Zerlotti Mercadante, Maria Eugenia; Silva, Josineudson Augusto II Vasconcelos [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2012)
The objective of this work was to estimate, by meta-analysis, the heritability (h(2)) and the genetic (r(g)) and phenotypic (r(f)) correlations of residual feed intake (RFI), and of its component traits in beef cattle from 19 breeds or genetic groups. Twenty-two scientific papers published from 1963 to 2011, from eight countries, totaling 52,637 cattle of ages from 28 days up to slaughter, were evaluated. The estimates of RFI, dry matter intake (DMI), average daily gain (ADG) and metabolic weight (BW0.75) were weighted by the inverse of sample variance. The variation between studies of h(2) for each trait was analyzed by weighted least squares. The effects of sex, country and breed were significant for h(2) of RFI, explaining 67% of variation between studies. For DMI, country and breed effects were significant and explained 96% of variation. Pooled estimates of h(2) were: 0.255+/-0.008, 0.278+/-0.012, 0.321+/-0.015, and 0.397+/-0.032 for RFI, DMI, ADG and BW0.75, respectively. Pooled estimates of genetic and phenotypic correlations were low between RFI and ADG and between RFI and BW0.75 (from -0.021+/-0.034 to 0.025+/-0.035), and moderate between RFI and DMI (0.636+/-0.035 and 0.698+/-0.041) and between DMI, ADG and BW0.75 (0.441+/-0.062 to 0.688+/-0.032). The trait RFI has lower heritability estimates than its components.

O objetivo deste trabalho foi estimar, por meio de meta-análise, a herdabilidade (h2) e as correlações genética (rg) e fenotípica (rf) do consumo alimentar residual (CAR), e das suas características componentes, em bovinos de 19 raças ou grupamentos genéticos. Foram utilizados 22 trabalhos científicos publicados entre 1963 e 2011, de oito países, o que totalizou 52.637 bovinos com idades que variaram de 28 dias até a idade de abate. As estimativas de CAR, consumo de matéria seca (CMS), ganho médio diário (GMD) e peso metabólico (PV0, 75) foram ponderadas pelo inverso da variância amostral. A variação da h2 de cada característica entre os estudos foi analisada por quadrados mínimos ponderados. Os efeitos de sexo, país e raça foram significativos para h2 de CAR e explicaram 67% da variação entre os estudos. Para CMS, os efeitos de país e raça foram significativos e explicaram 96% da variação. As estimativas combinadas de h2 foram: 0, 255±0, 008, 0, 278±0, 012, 0, 321±0, 015 e 0, 397±0, 032 para CAR, CMS, GMD e PV0, 75, respectivamente. As estimativas combinadas de correlação genética e fenotípica foram baixas entre CAR e GMD e entre CAR e PV0, 75 (de -0, 021±0, 034 a 0, 025±0, 035), e de média magnitude entre CAR e CMS (0, 636±0, 035 a 0, 698±0, 041) e entre CMS, GMD e PV0, 75 (0, 441±0, 062 a 0, 688±0, 032). O CAR apresenta estimativa de herdabilidade menor que a de suas características componentes.
Meta-analysis of genetic parameter estimates of residual feed intake and of its component traits in cattle
Keywords: dry matter intake; genetic correlation; feed efficiency; pooled estimates; heritability; metabolic weight